Psychological status of general population 1 year after the outbreak of COVID-19: a cross-sectional study based on SCL-90 - Chen, Xia; Hu, Yue; Deng, Yuan; Wang, Xin; Yang, Xiao; Wang, Ying; Lian, Yanli; Wang, Shiping; Xiang, Xinju; Liu, Chan; Wu, Fang; Chen, Shaochuan; et al. (Frontiers in Psychology, 2024)
The mental health of populations is usually affected after a disaster event. However, it is not known what the level of mental health of Chinese population one year after COVID-19, nor what factors influence it.Aim: This study aimed to examine the mental health status of general population in Chengdu one year after COVID-19, and then analyse influencing factors.This study is a cross-sectional survey based on the SCL-90 questionnaire.Continuous data were described as M and SD, and counting data were described as frequencies(n) and percentages(%). Chi-square test or Fisher's exact test were used for statistical inference, and significance variables were included in the binary logistic regression equation for multivariate analysis.Results : There were 172 participants with positive screening results. Age, marital status, number of kids, self-perceived health and the presence of chronic disease had an effect on screening results. Logistic regression analysis showed that age and self-perceived health were the main influencing factors.Discussion: Young people aged 18-19 and those who consider themselves not very healthy were at higher risk of poor mental health one year after the COVID-19 outbreak.Impact statement: Community institutions and community workers should focus on the mental health status of people one year after COVID-19, with a focus on people with poor self-perceived health and younger age groups, and take early preventive measures.